Pendampingan Penggunaan Dan Pemasaran Makanan Ringan Melalui Innovative Packaging Di Pulau Lance Batam - Edy Wibowo, Agung; Silitonga, Frangky; Kartika Cahayani; Sianipar, Baktivillo; Ardiansyah Saputra; ay; Senop Putra Perwira (PUSLITABMAS-Politeknik Pariwisata Batamc, 2024)
This PKM is carried out to enable lecturers and students together with the community to find the best solutions that can answer the problems experienced by the community, especially the use and marketing of Riang Food through innovative packaging on Lance Island for tourism activities which can be part of the driving force for improving the economy of Lance Island residents. This PKM activity has inspired the Lance community that Lance Island has products that are packaged into food that is worth selling and has its own charm. This PKM activity will produce the best way to package types of snacks such as crackers and dents. This activity consists of students and lecturers carrying out their tri dharma